A estética transcendental kantiana à luz de Strawson - Nobre, José Mariano (2008)
This work s objective is to make a literal interpretation of Kant s Aesthetic transcendental, the first pilaster of sustentation of the epistemology of Kant and to interpret it at Strawson s light. It contains the doctrine of sensitivity responsible for the intuitions, which rests on the concepts of space and time, and, with this, the tematização of two important questions. For Kant s philosophy in its epistemologic source what s the importance of the concepts of and time? How these concepts of space and time inscribe themselves with such statute as an investigatory task of metaphysics? The specification of the concepts of space and time as ingredients of the theories treated and enrolled in this work are segmented of the Aesthetic transcendental of Kant, and interpreted under Strawson s light. The research is divided in two chapter; first, constituted of two parts, the first part presents an introduction to the Aesthetic transcendental of Kant, to show the doctrine of the sensitivity which is part of with its forms space and time, authentic forms of the intuition. The second chapter, is constituted of four parts, that deal with the interpretation of the austere model of Strawson and related with Kant s transcendental Aesthetic. The conclusion of our work, about the declared objection of Strawson in its austere interpretation that refuses the idea of space and time, even keeping its a priori character, cannot be accepted. The apriority, the intuitivity and the ideality are theories non-separable in a coherent boarding of space and time of Kant s model of epistemology